Metal electrode with surface protective layer, preparation method thereof and alkali metal battery
By forming a fluorine-doped graphene oxide layer and a fluorine-rich SEI film on the alkali metal electrode, the surface protective layer MES is formed, which solves the dendrite growth problem caused by the interface instability of the metal electrode and significantly improves the stability of the battery and cycle life.
Patent Information
- Application Number
- CN202211141991.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-20
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-09-20
AI Technical Summary
During the circulation, metal electrodes cause dendrites to grow due to interface instability, which in turn affects the stability and performance of the battery.
A fluorine-doped graphene oxide layer is formed on the alkali metal electrode, and a fluorine-rich SEI film is formed through charge and discharge cycles to form a surface protective layer MES common to graphene and SEI film.
By forming a stable surface protective layer MES, the growth of dendrites is effectively suppressed, the stability of metal electrodes is improved, and the cycle life of the battery is extended.
Smart Images

Figure CN115394957B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a metal electrode with a surface protective layer, a preparation method thereof and an alkali metal battery. Background Art
[0002] Compared with traditional negative electrode materials, metal negative electrodes have lower redox potentials and higher specific capacities, making them ideal negative electrode materials for high energy density batteries. However, metal negative electrodes exhibit extremely high reactivity and are easily in contact with electrolytes to form unstable solid electrolyte interfaces (SEI). Metal electrodes with unstable interfaces cannot control the morphology of plating / stripping during the charge and discharge process, resulting in uncontrollable growth of metal dendrites. At the same time, the volume change caused by the uneven diffusion and deposition of metal ions will aggravate the growth of dendrites. These reasons will lead to the rupture of the interfacial SEI and the consumption of active substances. To date, there are still huge obstacles to the practical application of metal batteries.
[0003] In recent years, in-depth research has been conducted on metal electrode design, electrolyte improvement, and dendrite growth mechanism. For example, constructing a three-dimensional framework to mitigate the volume change of metal electrodes and uniform ion flux, or designing liquid alloys as metal negative electrodes to inhibit dendrite growth. These research methods can solve some problems of metal electrodes to a certain extent, but they cannot play a role in real large-scale use.
[0004] Recent studies have shown that stable interfaces play a vital role in the stable cycling of metal batteries. For metal anodes, the solid electrolyte interface (SEI) acts as an ionic conductor between the electrode and the electrolyte, which can effectively avoid continuous side reactions and regulate metal nucleation. The naturally formed SEI has poor mechanical properties and cannot adapt to the volume changes during the plating / stripping process. The rupture of the SEI exacerbates the growth of dendrites. The SEI ruptures to form dendrites, which changes the electric field distribution and ion flux. The constantly exposed new metal surface will continuously produce new SEI, resulting in the continuous consumption of electrolyte and metal. The instability of the interface will lead to the rapid decay of the Coulomb efficiency (CE), thereby reducing the rate capability of metal batteries. To solve these problems, researchers have conducted a variety of studies and explorations. Changing the solvent or solvation structure, adding functionalized electrolyte additives, and changing the electrolyte concentration may be effective. These methods can establish a relatively stable interface on the metal surface and inhibit the growth of dendrites in the initial cycle. However, the SEI formed by optimizing the electrolyte alone does not produce excellent mechanical stability, and the scalability and cost are not suitable for large-scale production.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The purpose of the present invention is to provide a metal electrode with a surface protective layer, a preparation method thereof and an alkali metal battery, aiming to form a stable SEI layer on the metal electrode during the cycle process, thereby greatly improving the stability of the metal electrode.
[0007] The present invention is achieved in that:
[0008] In a first aspect, the present invention provides a metal electrode with a surface protection layer, comprising an alkali metal electrode and a surface protection layer supported on the alkali metal electrode, wherein the surface protection layer comprises a fluorine-doped graphene oxide layer.
[0009] In an optional embodiment of the present invention, the alkali metal electrode is selected from any one of potassium foil and lithium foil, and the fluorine-doped graphene oxide layer is loaded on one side surface of the alkali metal electrode;
[0010] Preferably, the thickness of the alkali metal electrode is 5-50 μm, and the thickness of the fluorine-doped graphene oxide layer is 0.5-2 μm.
[0011] In an optional embodiment of the present invention, the surface protection layer further includes a fluorine-containing SEI film, and the fluorine-containing SEI film is supported on the fluorine-doped graphene oxide layer.
[0012] In an optional embodiment of the present invention, a metal electrode with a surface protective layer is provided, comprising an alkali metal electrode and a surface protective layer loaded on the alkali metal electrode, the surface protective layer comprising a graphene layer and a fluorine-containing SEI film, and the graphene layer is located between the alkali metal electrode and the fluorine-containing SEI film.
[0013] In a second aspect, the present invention also provides a method for preparing a metal electrode having a surface protection layer, comprising: forming a fluorine-doped graphene oxide layer on an alkali metal electrode.
[0014] In an optional embodiment of the present invention, the method comprises: attaching fluorine-doped graphene oxide to the surface of a carrier to form a fluorine-doped graphene oxide layer on the surface of the carrier; transferring the fluorine-doped graphene oxide layer on the surface of the carrier to the alkali metal electrode by rolling;
[0015] Wherein, the carrier is selected from any one of copper foil and aluminum foil, preferably copper foil;
[0016] Preferably, the method further comprises using the alkali metal electrode having the fluorine-doped graphene oxide layer as the negative electrode of the battery to perform charge and discharge cycles to form a fluorine-containing SEI film on the fluorine-doped graphene oxide layer.
[0017] In an optional embodiment of the present invention, the preparation process of fluorine-doped graphene oxide includes: mixing graphene oxide with a dispersant and dispersing the graphene oxide to obtain a dispersion, uniformly mixing the fluoride salt with the dispersion, adding methanol to react, filtering to obtain a fluorinated product, and washing and drying the fluorinated product;
[0018] Preferably, the dispersant is o-dichlorobenzene; the fluoride salt is diethylaminosulfur trifluoride;
[0019] Preferably, the concentration of the dispersion is 0.5-2 mg / mL, the volume ratio of the dispersion to the fluoride salt is 50-70:1, and the volume ratio of the dispersion to methanol is 1-2:1;
[0020] Preferably, the fluoride salt is mixed with the dispersion at -5°C to 5°C, subjected to ultrasonic treatment for 4-8 hours, and then stirred at 15-25°C for 2-4 days.
[0021] In an optional embodiment of the present invention, the process of attaching fluorine-doped graphene oxide to the surface of a carrier comprises: mixing fluorine-doped graphene oxide with an organic solvent and ultrasonically obtaining a suspension, immersing the carrier in a container filled with water, injecting the suspension on the water surface, and when the suspension forms a self-assembled film on the water surface, lifting the carrier in the water so that the self-assembled film is loaded on the carrier, and obtaining a carrier with a fluorine-doped graphene oxide layer loaded on the surface after drying;
[0022] Preferably, after lifting the carrier in the water, the carrier is immersed in the water again and lifted, and the operation is repeated until the thickness of the self-assembled film on the carrier is 0.5-2 μm; wherein the thickness of the carrier is 10-15 μm;
[0023] Preferably, the drying process comprises: first drying the carrier with the self-assembled film on a hot plate at 70-90° C. for 2-5 min, and then drying in a vacuum oven at 70-90° C. for 8-20 h.
[0024] In an optional embodiment of the present invention, the process of transferring the fluorine-doped graphene oxide layer on the surface of the carrier to the alkali metal electrode comprises: stacking the carrier having the fluorine-doped graphene oxide layer and the alkali metal foil, wrapping the stacked components with a protective film, pressing the stacked components using a roller press, and removing the protective film and the carrier after rolling;
[0025] Preferably, the roller distance is 70%-90% of the total thickness of the stacked assembly, and the rolling speed is 0.5-1.5 cm.s -1 ;
[0026] Preferably, the protective film is a plastic film.
[0027] In a third aspect, the present invention further provides an alkali metal battery, wherein the negative electrode is the metal electrode with a surface protective layer in the above embodiment;
[0028] Preferably, the preparation process of the negative electrode comprises: cutting the metal electrode into a disc shape of 1-2 cm.
[0029] In an optional embodiment of the present invention, it also includes a positive electrode, an electrolyte and a separator;
[0030] Preferably, the preparation process of the positive electrode comprises: uniformly mixing a conductive agent, a binder and an active material with a dispersing solvent to obtain a slurry, coating the slurry on a copper foil current collector, and drying; wherein the mass ratio of the conductive agent, the binder and the active material is 5-7:2-4:1;
[0031] Preferably, the conductive agent is acetylene black conductive agent, the binder is PVDF binder, the active material is Prussian blue material, the dispersing solvent is N-methyl-2-pyrrolidone, and the loading amount of the active material is controlled to be 0.8-1.2 mg.cm during coating. -2 ;
[0032] Preferably, the membrane is fiberglass or polypropylene.
[0033] The present invention has the following beneficial effects: by introducing a fluorine-doped graphene oxide layer on an alkali metal electrode, the carbon-fluorine bond is broken through charge and discharge cycles during use and a fluorine-rich SEI film is formed on the surface of the electrode graphene, and the graphene and the SEI film together form a surface protection layer MES, which can adjust the flatness and uniformity of the electric field, so that the metal electrode forms a stable SEI layer during the cycle process, effectively inhibits the growth of dendrites, stabilizes the metal interface, and thus greatly improves the stability of the metal electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0035] Figure 1 Schematic diagram of the preparation and homogenization electric field of MES; Figure 1 In the figure, A represents the schematic diagram of human skin and surface structure; B represents the schematic diagram of the protective layer structure on the metal electrode surface; C represents the SEM image of K@MES; D represents the TEM image of K@MES; E represents the preparation and transfer process of the MES main material and the corresponding SEM image; F represents the AFM image of F-GO on the copper foil surface; G represents the surface electric field of the electrode and the corresponding ion distribution during the initial K electroplating process;
[0036] Figure 2 DFT calculations and XPS spectra; Figure 2A represents the lattice parameters of K, fluorine-doped graphene, potassium fluoride (KF) and graphene; B represents the XPS measurement spectrum; C and D represent the high-resolution XPS spectrum of GO; E and G represent the high-resolution XPS spectrum of F-GO; H and I represent the high-resolution XPS spectrum of F-GO after cycling; J represents the infrared spectra of GO, F-GO and F-GO after cycling;
[0037] Figure 3 Interface changes and surface characterization diagram of metal electrodes; Figure 3 In the figure, A is a schematic diagram of the interface changes of K metal electrodes in different forms; B is a SEM image of the surface of K metal in different forms after cycling; C is an in situ optical microscope image of K deposition at different times on the surfaces of three different potassium metal electrodes (i corresponds to bare K, ii corresponds to K@GO, and iii corresponds to K@MES);
[0038] Figure 4 This is the electrochemical performance test diagram of K metal battery; Figure 4 In the figure, A represents the CV curve; B represents the Tafel curve; C represents the electrochemical impedance spectroscopy curve of the K|K symmetric battery, with a scan rate of 0.2 mVs -1 , the voltage is between 2 and 0.2; D is the voltage curve of the K|K symmetric battery at different current densities; E is the voltage curve of the K|K symmetric battery at 0.5 mA cm -2 The fixed current density and 0.5 mAh cm -2 The KFSI electrolyte is used at a capacity of 1.5 %; F represents the constant current K electrodeposition / stripping voltage curve of the KPF6 electrolyte; G represents the functional relationship between the coulombic efficiency and the number of cycles of the Cu|K asymmetric battery using the KFSI electrolyte; H represents the corresponding voltage curve; I represents the comparison chart of the cycle life of the Cu|K and K|K batteries corresponding to the K@MES and the disclosed negative electrodes;
[0039] Figure 5 Li|Li symmetric cells based on LiFSI electrolyte with different lithium metal electrodes at 1 mA cm -2 A fixed current density of 1 mAh cm -2 Constant current lithium plating / stripping voltage curve under capacity;
[0040] Figure 6 Li|Li symmetric cells based on LiPF6 electrolyte with different lithium metal electrodes at 1 mA cm -2 A fixed current density of 1 mAh cm -2 Constant current lithium plating / stripping voltage curve under capacity;
[0041] Figure 7 It is the voltage curve test result; Figure 7A in the figure represents the functional relationship between the Coulombic efficiency and the cycle number of the Cu|K asymmetric battery based on LiFSI electrolyte; Figure 7 B in the figure indicates the corresponding voltage curve; Figure 7 C in the figure represents the voltage curve of Li|Li symmetric battery at different current densities;
[0042] Figure 8 The electrochemical performance of button cells based on KPF6 electrolyte, K (negative electrode) | PB (Prussian blue positive electrode); Figure 8 A in the middle represents the cycle performance comparison chart of full batteries based on three different K metal positive electrodes; Figure 8 B means 500mA g -1 The charge and discharge voltage curves at the current density of Figure 8 C in the middle represents the rate performance curve; Figure 8 D in the middle represents the charge and discharge voltage curves of the corresponding cycle numbers; Figure 8 E represents the full battery based on K@MES negative electrode at 1000mA g -1 Long-term cycle performance curve under current density;
[0043] Fig. 9 Electrochemical performance of button cells based on KFSI electrolyte, K (negative electrode) | PB (Prussian blue positive electrode); Fig. 9 A represents the full battery based on three different K metal cathodes at 500 mA g -1 Comparison of cycling performance at current density of; Fig. 9 B in the figure represents the charge and discharge voltage curve; Fig. 9 C in the middle represents the rate performance curve; Fig. 9 D in the figure shows the charge and discharge voltage curves at the corresponding cycle numbers. DETAILED DESCRIPTION
[0044] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0045] The embodiment of the present invention provides a method for preparing a metal electrode with a surface protective layer, which forms a fluorine-doped graphene oxide layer on an alkali metal electrode, breaks the carbon-fluorine bond through charge and discharge cycles during use, and forms a fluorine-rich SEI film on the surface of the electrode graphene, and the graphene and SEI film together form a surface protective layer MES. Specifically, the method comprises the following steps:
[0046] S1. Preparation of fluorine-doped graphene oxide
[0047] The preparation process of fluorine-doped graphene oxide is not limited, and it can be prepared by a commonly used method for preparing graphene oxide doped materials.
[0048] In some embodiments, the preparation process of fluorine-doped graphene oxide includes: mixing graphene oxide with a dispersant and dispersing the graphene oxide to obtain a dispersion, after evenly mixing the fluoride salt with the dispersion, a mild liquid phase reaction between the graphene oxide and DAST is carried out to prepare fluorinated graphene, methanol is added to quench the reaction, and a fluorinated product is obtained by filtering, and the fluorinated product is washed and dried to obtain powdered fluorine-doped graphene oxide.
[0049] In some embodiments, the dispersant is o-dichlorobenzene; the fluoride salt is diethylaminosulfur trifluoride. The dispersant and the fluoride salt can be selected from the above raw materials, and can be one or more, which are not limited here. For example, the dispersant can be o-dichlorobenzene, and the fluoride salt can be diethylaminosulfur trifluoride.
[0050] In order to better control the fluorine content, the inventors optimized the amount of raw materials used in the reaction process: the concentration of the dispersion is 0.5-2 mg / mL, the volume ratio of the dispersion and the fluoride salt is 50-70:1, and the volume ratio of the dispersion and methanol is 1-2:1. Specifically, the concentration of the dispersion is to control the amount of graphene oxide and the dispersant, so that the concentration of the dispersion is 0.5 mg / mL, 1.0 mg / mL, 1.5 mg / mL, 2.0 mg / mL, etc.; the volume ratio of the dispersion and the fluoride salt can be 50:1, 60:1, 70:1, etc.; the volume ratio of the dispersion and methanol can be 1:1, 1.5:1, 2:1, etc. Since graphene oxide is not easy to disperse, the dispersion can be prepared by long-term and vigorous stirring to promote the dispersion of graphene oxide.
[0051] In some embodiments, the fluoride salt is mixed with the dispersion at -5°C to 5°C (e.g., -5°C, 0°C, 5°C, etc.), ultrasonically treated for 4-8 hours, and then stirred at 15-25°C (i.e., room temperature) for 2-4 days. The fluoride salt and graphene oxide can be evenly dispersed by ultrasonication combined with long-term stirring.
[0052] It should be added that the fluorinated product can be washed in any manner and can be thoroughly washed with ethanol, acetone and deionized water to remove impurities, and then dried in vacuum at 60° C. for 12 hours.
[0053] S2. Preparation of Cu@F-GO
[0054] Fluorine-doped graphene oxide is attached to the surface of a carrier to form a fluorine-doped graphene oxide layer on the surface of the carrier; the carrier is selected from any one of copper foil and aluminum foil, preferably copper foil. Copper foil is easy to obtain, has a flat surface, and is easy to form a uniform coating. There is no limit to the method of attaching fluorine-doped graphene oxide to the carrier, as long as the fluorine-doped graphene oxide can be attached to form a stable coating.
[0055] In some embodiments, the Langmuir-Blodgett method can be used to construct the main material of the required metal electrode surface protection layer on the copper foil. The specific steps include: the process of attaching fluorine-doped graphene oxide to the surface of the carrier includes: mixing fluorine-doped graphene oxide with an organic solvent and ultrasonically obtaining a suspension, immersing the carrier in a container filled with water, injecting the suspension on the water surface, and when the suspension forms a self-assembled film on the water surface, lifting the carrier in the water so that the self-assembled film is loaded on the carrier, and drying to obtain a carrier with a fluorine-doped graphene oxide layer loaded on the surface. In actual operation, when the self-assembled film covers about 70% of the water surface, the self-assembled F-GO film is coated on the surface of the copper foil by simultaneously lifting the copper foil immersed in water.
[0056] In order to achieve the desired thickness, the carrier is lifted out of the water, then immersed in the water again and lifted out, and the operation is repeated until the thickness of the self-assembled film on the carrier is 0.5-2 μm; wherein the thickness of the carrier is 10-15 μm. It is preferable to control the thickness of the self-assembled film within the above range, which is conducive to the formation of a fluorine-doped graphene oxide layer of appropriate thickness on the alkali metal later.
[0057] In some embodiments, the drying process includes: first drying the support with the self-assembled film on a hot plate at 70-90° C. (such as 70° C., 80° C., 90° C., etc.) for 2-5 min, and then drying in a vacuum oven at 70-90° C. for 8-20 h to obtain Cu@F-GO. The organic solvent used to disperse the fluorine-doped graphene oxide, such as pure ethanol, is removed by drying.
[0058] S3. Preparation of alkali metal@F-GO
[0059] The fluorine-doped graphene oxide layer on the surface of the carrier is transferred to the alkali metal electrode by rolling. In the actual operation process, the carrier with the fluorine-doped graphene oxide layer is stacked with the alkali metal foil, the stacked components are wrapped with a protective film, and the stacked components are pressed by a roller press. After rolling, the protective film and the carrier are removed. The protective film can protect the alkali metal foil and prevent the alkali metal foil from oxidation in the air; the stacked components are evenly pressed by a roller press, so that the fluorine-doped graphene oxide layer is transferred to the alkali metal foil. After the transfer, the fluorine-doped graphene oxide layer is located on one side of the alkali metal foil.
[0060] To further achieve the effect of uniform pressing, the roller distance is 70%-90% (such as 70%, 80%, 90%, etc.) of the total thickness of the stacked assembly, and the rolling speed is 0.5-1.5 cm.s -1 (e.g. 0.5cm.s -1 、1.0cm.s -1 、1.5cm.s -1 After rolling, the plastic film was removed and the copper foil was peeled off to obtain the alkali metal@F-GO.
[0061] In some embodiments, the protective film is a plastic film, which can provide good protection for the alkali metal foil. The alkali metal foil is selected from any one of potassium foil and lithium foil.
[0062] S4. Formation of SEI film
[0063] The alkali metal electrode with fluorine-doped graphene oxide layer is used as the negative electrode of the battery for charge and discharge cycles to form a fluorine-containing SEI film on the fluorine-doped graphene oxide layer. The charge and discharge cycles break the carbon-fluorine bond and form a fluorine-rich SEI film on the surface of the electrode graphene. The graphene and SEI film together form a surface protection layer MES, and the resulting electrode is the alkali metal @ MES.
[0064] An embodiment of the present invention provides a metal electrode with a surface protective layer, including an alkali metal electrode and a surface protective layer loaded on the alkali metal electrode, wherein the surface protective layer includes a fluorine-doped graphene oxide layer, which can be prepared by the above preparation method, so that the fluorine-doped graphene oxide layer is loaded on one side surface of the alkali metal electrode.
[0065] Specifically, the alkali metal electrode is selected from any one of potassium foil and lithium foil, the thickness of the alkali metal electrode is 5-50 μm, and the thickness of the fluorine-doped graphene oxide layer is 0.5-2 μm.
[0066] In some embodiments, a metal electrode with a surface protective layer is provided, comprising an alkali metal electrode and a surface protective layer supported on the alkali metal electrode, the surface protective layer comprising a graphene layer and a fluorine-containing SEI film, the graphene layer being located between the alkali metal electrode and the fluorine-containing SEI film. The fluorine-containing SEI film is supported on the graphene layer, and the fluorine-containing SEI film is formed on the surface of the electrode graphene by breaking the carbon-fluorine bond through charge and discharge cycles.
[0067] An embodiment of the present invention also provides an alkali metal battery, whose negative electrode is the metal electrode with a surface protective layer in the above-mentioned embodiment. Through the improvement of the negative electrode material, since the negative electrode has extremely high stability, the growth of dendrites can be effectively inhibited, and the metal interface can be stabilized, which is beneficial to further improve the performance of the alkali metal battery.
[0068] In actual operation, the preparation process of the negative electrode includes: cutting the metal electrode prepared by the above preparation method into a 1-2 cm disc shape and using it as the negative electrode of the alkali metal battery.
[0069] Furthermore, it also includes a positive electrode, an electrolyte and a separator. The materials of the positive electrode, the electrolyte and the separator are not limited and can be conventional materials used for alkali metal batteries. The electrolyte is conventionally adjusted according to the different negative electrodes. The alkali metal battery is a potassium metal battery or a lithium metal battery, and the electrolyte composition can be adjusted according to the specific type.
[0070] In some embodiments, the preparation process of the positive electrode includes: mixing a conductive agent, a binder and an active material with a dispersing solvent to obtain a slurry, coating the slurry on a copper foil collector, and drying; wherein the mass ratio of the conductive agent, the binder and the active material is 5-7:2-4:1 (such as 5:2:1, 6:3:1, 7:4:1, etc.); the conductive agent may be but not limited to acetylene black conductive agent, the binder may be but not limited to PVDF binder, the active material may be but not limited to Prussian blue material, the dispersing solvent may be but not limited to N-methyl-2-pyrrolidone, and the loading amount of the active material is controlled to be 0.8-1.2 mg.cm during coating. -2 , such as 0.8mg.cm -2 、1.0mg.cm -2 、1.2mg.cm -2 The drying process may be baking and drying at 80° C. for 24 hours. When the alkali metal battery is a potassium metal battery or a lithium metal battery, the positive electrode may be prepared by the above method.
[0071] In some embodiments, the separator is glass fiber or polypropylene. For potassium metal batteries, the separator can be glass fiber (Whatman, GF / D); for lithium metal batteries, the separator can be polypropylene.
[0072] For potassium metal batteries, the electrolyte composition can be the following two: (1) potassium bis(fluorosulfonyl)amide (KFSI, purity 98%, 3 mol L -1 ) dispersed in 1,2-dimethoxyethane (DME); (2) potassium hexafluorophosphate (KPF6, purity 99%, 0.8 mol L -1 ) is dispersed in ethylene carbonate (EC): dimethyl carbonate (DMC) = 1:1 (v:v).
[0073] For lithium metal batteries, the electrolyte composition can be the following two: (1) lithium bis(fluorosulfonyl)imide (LiFSI, purity 99%, 3 mol L -1 ) dispersed in 1,2-dimethoxyethane (DME); (2) LiPF6 (LiPF6, purity 99% 0.8 mol L -1) is dispersed in ethylene carbonate (EC): dimethyl carbonate (DMC): diethyl carbonate (DEC) = 0.25:1:1 (v / v / v).
[0074] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0075] Example 1
[0076] This embodiment provides a method for preparing a potassium metal symmetric battery with a K@MES negative electrode, comprising the following steps:
[0077] (1) Preparation of K@F-GO anode
[0078] Preparation of fluorine-doped graphene oxide (F-GO): 150 mL of o-dichlorobenzene (DCB) and 0.15 g of graphene oxide (GO) powder were added to a 250 mL PTFE flask in sequence; the mixture was vigorously stirred for more than 12 hours to promote GO dispersion; then, 2.5 mL of diethylaminosulfur trifluoride (DAST) was added dropwise to the dispersion for 10 minutes while maintaining a temperature of 0°C; the reaction mixture was then ultrasonically treated for 6 hours and then stirred at room temperature for 3 days; then, the reaction was quenched by carefully adding 100 mL of methanol. Finally, the mixture was filtered to obtain the fluorinated product, which was then thoroughly washed with ethanol, acetone and deionized water to remove impurities, and vacuum dried at 60°C for 12 hours to obtain fluorine-doped graphene oxide (F-GO).
[0079] Preparation of Cu@F-GO (i.e. coating F-GO on the surface of copper foil): the prepared fluorine-doped graphene oxide material is dispersed in pure ethanol, and then ultrasonically treated for 60 minutes to obtain a F-GO suspension; the copper foil is cut into (10cm*20cm size), and then the copper foil is immersed in a beaker filled with water, and the required F-GO suspension is continuously injected on the water surface to prepare the main material of the metal electrode surface protective layer. When the self-assembled film covers about 70% of the water surface, the self-assembled F-GO film is coated on the surface of the copper foil by simultaneously lifting the copper foil immersed in water; and the above process is repeated to finally obtain a (0.5-2 micron) F-GO film; then the copper foil coated with the F-GO film is placed on a hot plate at 80°C and dried for 3 minutes, and dried in a vacuum oven at 80°C for more than 12 hours to obtain Cu@F-GO.
[0080] K@F-GO was prepared by transferring F-GO from the copper foil surface to the potassium electrode surface through a roller pressing process: Cu@F-GO and potassium foil were stacked together and sandwiched between two plastic films under argon atmosphere; the stacked components were then uniformly pressed using a roller press, with a roller distance of about 80% of the total thickness of the stacked components and a rolling speed of 1 cm s -1 ; After rolling, the plastic film was removed and the copper foil was peeled off to obtain K@F-GO.
[0081] (2) Electrolyte
[0082] 3M potassium bis(fluorosulfonyl)amide (KFSI, purity 98%, 3 mol L -1 ) is evenly dispersed in 1,2-dimethoxyethane (DME).
[0083] (3) Diaphragm
[0084] Glass fiber (Whatman, GF / D).
[0085] (4) Assembly and disassembly of potassium metal batteries
[0086] The 2032-sized potassium metal coin cells were assembled and disassembled in an argon-filled glove box (moisture and oxygen concentrations were kept below 0.5 ppm).
[0087] (5) Performance testing
[0088] Potassium metal battery charge and discharge cycle: The potassium metal battery is charged and discharged in cycles. The deposition of K can promote the breaking of the carbon-fluorine bond of fluorine-doped graphene oxide. The fluorine-doped graphene oxide is reduced to graphene. At the same time, the continuous release of fluorine elements will form a fluorine-rich SEI on the surface. The graphene layer and the fluorine-rich SEI film together form a surface protection layer MES with good mechanical strength and stability. The graphene and fluorine-rich SEI of the surface protection layer MES are similar to the protection of the dermis and epidermis of human skin to internal cells and muscles, effectively improving the surface flatness of the metal electrode and providing a uniform electric field.
[0089] Example 2 (Potassium metal symmetric battery based on K@MES negative electrode)
[0090] The only difference from Example 1 is that the electrolyte of this example is 0.8M potassium hexafluorophosphate (KPF6, purity 99%, 0.8mol L -1 ) is uniformly dispersed in ethylene carbonate (EC) and dimethyl carbonate (DMC) (v:v=1:1).
[0091] Example 3 (Potassium-copper asymmetric battery based on K@MES negative electrode)
[0092] The difference from Example 1 is that the counter electrode of this embodiment is Cu, and the rest is the same as Example 1.
[0093] Comparative Example 1
[0094] A potassium metal battery based on a bare potassium foil negative electrode, that is, the potassium foil is directly used as the negative electrode, and the rest is the same as Example 1.
[0095] Comparative Example 2
[0096] Potassium metal battery based on K@GO negative electrode, the preparation method of K@GO negative electrode is the same as that of K@MES, and the rest is the same as Example 1. That is, the only difference from Example 1 is that fluorine is not introduced during the preparation process.
[0097] Comparative Example 3
[0098] A potassium metal battery based on a bare potassium foil negative electrode, that is, the potassium foil is directly used as the negative electrode, and the rest is the same as Example 2.
[0099] Comparative Example 4
[0100] Potassium metal battery based on K@GO negative electrode, the preparation method of K@GO negative electrode is the same as that of K@MES; the rest is the same as Example 2. That is, the only difference from Example 2 is that fluorine is not introduced during the preparation process.
[0101] Comparative Example 5
[0102] A potassium metal battery based on a bare potassium foil negative electrode, that is, the potassium foil is directly used as the negative electrode; the rest is the same as Example 3.
[0103] Comparative Example 6
[0104] Potassium metal battery based on K@GO negative electrode, the preparation method of K@GO negative electrode is the same as that of K@MES; the rest is the same as Example 3. That is, the only difference from Example 3 is that fluorine is not introduced during the preparation process.
[0105] Example 4
[0106] Lithium metal symmetric battery based on Li@MES anode:
[0107] The difference from Example 1 is that the negative electrode of this embodiment is a Li@MES electrode, and its preparation process is the same as that of K@MES, except that the electrode is replaced by lithium foil from potassium foil during the rolling process transfer process; the electrolyte is 3M lithium bis(fluorosulfonyl)imide (LiFSI, purity 99%, 3 mol L -1 ) in 1,2-dimethoxyethane (DME); the diaphragm is polypropylene.
[0108] Example 5
[0109] Lithium metal symmetric battery based on Li@MES anode:
[0110] The difference from Example 4 is that the electrolyte of this example is 0.8M lithium hexafluorophosphate (LiPF6, purity 99%, 0.8mol L -1 ) is uniformly dispersed in ethylene carbonate (EC) and dimethyl carbonate (DMC) (v:v=1:1).
[0111] Example 6
[0112] Potassium-copper asymmetric battery based on K@MES negative electrode:
[0113] The difference from Example 4 is that the counter electrode of this embodiment is Cu, and the rest is consistent with Example 4.
[0114] Comparative Example 7
[0115] A lithium metal battery based on a bare lithium foil negative electrode, that is, the lithium foil is directly used as the negative electrode; the rest is the same as Example 4.
[0116] Comparative Example 8
[0117] The preparation method of the lithium metal battery based on the Li@GO negative electrode is the same as that of the Li@MES; the rest is the same as that of Example 4. That is, the only difference from Example 4 is that fluorine is not introduced during the preparation process.
[0118] Comparative Example 9
[0119] A lithium metal battery based on a bare lithium foil negative electrode, that is, the lithium foil is directly used as the negative electrode; the rest is the same as Example 5.
[0120] Comparative Example 10
[0121] The preparation method of the lithium metal battery based on the Li@GO negative electrode is the same as that of the Li@MES; the rest is the same as that of Example 5. That is, the only difference from Example 5 is that fluorine is not introduced during the preparation process.
[0122] Comparative Example 11
[0123] A lithium metal battery based on a bare lithium foil negative electrode, that is, the lithium foil is directly used as the negative electrode; the rest is the same as Example 6.
[0124] Comparative Example 12
[0125] The lithium metal battery based on Li@GO negative electrode, the preparation method of Li@GO negative electrode is the same as that of lithium@MES; the rest is the same as Example 6. That is, the only difference from Example 6 is that fluorine is not introduced during the preparation process.
[0126] Example 7
[0127] Potassium metal full battery based on K@MES anode:
[0128] (1) Preparation of K@F-GO anode:
[0129] Preparation of fluorine-doped graphene oxide (F-GO): 150 mL of o-dichlorobenzene (DCB) and 0.15 g of graphene oxide (GO) powder were added to a 250 mL PTFE flask in sequence; the mixture was vigorously stirred for more than 12 hours to promote GO dispersion; thereafter, 2.5 mL of diethylaminosulfur trifluoride (DAST) was added dropwise to the dispersion for 10 minutes while maintaining a temperature of 0°C; the reaction mixture was then ultrasonically treated for 6 hours and then stirred at room temperature for 3 days; then, the reaction was quenched by carefully adding 100 mL of methanol; finally, the mixture was filtered to obtain the fluorinated product, which was then thoroughly washed with ethanol, acetone and deionized water to remove impurities, and vacuum dried at 60°C for 12 hours to obtain fluorine-doped graphene oxide (F-GO).
[0130] Preparation of Cu@F-GO (i.e., coating F-GO on the surface of copper foil): the prepared fluorine-doped graphene oxide material is dispersed in pure ethanol, and then ultrasonically treated for 60 minutes to obtain a F-GO suspension; the copper foil is cut into any size, and then the copper foil is immersed in a beaker filled with water, and the desired F-GO suspension is continuously injected on the water surface to prepare the main material of the metal electrode surface protective layer. When the self-assembled film covers about 70% of the water surface, the self-assembled (0.5-2 micron thick) F-GO film is coated on the surface of the copper foil by simultaneously lifting the copper foil immersed in water; and the above process is repeated to finally obtain a F-GO film of the desired thickness; then the copper foil coated with the F-GO film is placed on a hot plate at 80°C and dried for 3 minutes, and dried in a vacuum oven at 80°C for more than 12 hours to obtain Cu@F-GO.
[0131] Preparation of K@F-GO (i.e., transferring F-GO from the copper foil surface to the potassium electrode surface by a roller pressing process): Cu@F-GO and potassium foil were stacked together and sandwiched between two plastic films under argon atmosphere; the stacked components were then uniformly pressed using a roller press, with a roller distance of approximately 80% of the total thickness of the stacked components and a rolling speed of 1 cm s -1 ; After rolling, the plastic film was removed and the copper foil was peeled off to obtain K@F-GO.
[0132] (2) Preparation of Prussian blue (PB) positive electrode
[0133] Acetylene black conductive agent: PVDF binder: active material Prussian blue material were mixed in a weight ratio of 6:3:1 in N-methyl-2-pyrrolidone (NMP) (AR, 99%, Aladdin) solution and stirred for more than 12 hours. The slurry was then coated on a copper foil collector and dried at 80°C for 24 hours to obtain a positive electrode. The active material loading of the positive electrode was about 1.0 mg cm -2 .
[0134] (3) Electrolyte
[0135] 3M potassium bis(fluorosulfonyl)amide (KFSI, purity 98%, 3 mol L -1 ) is evenly dispersed in 1,2-dimethoxyethane (DME).
[0136] (4) Diaphragm
[0137] Glass fiber (Whatman, GF / D).
[0138] (5) Assembly and disassembly of potassium metal batteries
[0139] The 2032-sized potassium metal coin cells were assembled and disassembled in an argon-filled glove box (moisture and oxygen concentrations were kept below 0.5 ppm).
[0140] (6) Potassium metal battery charge and discharge cycle
[0141] The potassium metal battery is charged and discharged in cycles. The deposition of K can promote the breaking of the carbon-fluorine bond of fluorine-doped graphene oxide, and the fluorine-doped graphene oxide is reduced to graphene. At the same time, the continuous release of fluorine elements will form a fluorine-rich SEI on the surface. The graphene layer and the fluorine-rich SEI film together form a surface protection layer MES with good mechanical strength and stability. The graphene and fluorine-rich SEI of the surface protection layer MES are similar to the protection of the dermis and epidermis of human skin to internal cells and muscles, effectively improving the surface flatness of the metal electrode and providing a uniform electric field.
[0142] Example 8 (Potassium metal full battery based on K@MES negative electrode)
[0143] The only difference from Example 7 is that the electrolyte of this example is 0.8M lithium hexafluorophosphate (LiPF6, purity 99%, 0.8mol L -1 ) is uniformly dispersed in ethylene carbonate (EC) and dimethyl carbonate (DMC) (v:v=1:1).
[0144] Comparative Example 13
[0145] A potassium metal full battery based on a bare potassium foil negative electrode, that is, the potassium foil is directly used as the negative electrode; the rest is the same as Example 7.
[0146] Comparative Example 14
[0147] Potassium metal battery based on K@GO negative electrode, the preparation method of K@GO negative electrode is the same as that of K@MES; the rest is the same as Example 7. That is, the only difference from Example 7 is that fluorine is not introduced during the preparation process.
[0148] Comparative Example 15
[0149] A potassium metal full battery based on a bare potassium foil negative electrode, that is, the potassium foil is directly used as the negative electrode; the rest is the same as Example 8.
[0150] Comparative Example 16
[0151] Potassium metal battery based on K@GO negative electrode, the preparation method of K@GO negative electrode is the same as that of K@MES; the rest is the same as Example 8. That is, the only difference from Example 8 is that fluorine is not introduced during the preparation process.
[0152] Test Example 1
[0153] like Figure 1 As shown, a skin-like bionic protective layer was constructed ( Figure 1 A)-Metal Electrode Surface Protective Layer (MES) Figure 1 (B) It improves the interface stability and protects the metal electrode, inhibiting the growth of dendrites.
[0154] MES is composed of GO and a fluorine-rich enhanced SEI film ( Figure 1 , C and D).
[0155] The core material of MES is fluorine-doped graphene oxide, and the synthesis method is as follows Figure 1 As shown in E, first, GO is fluorinated, and the oxygen-containing functional groups (including carboxyl, hydroxyl, etc.) in GO are partially replaced by fluorine atoms to become fluorine-doped graphene oxide (F-GO). Then the treated F-GO is dispersed in an alcohol solution and ultrasonically treated to form a uniform suspension. The prepared suspension is slowly dripped into deionized water, and the F-GO on the surface is slowly extracted by copper foil. After multiple extractions, a film of a certain thickness can be obtained, and then the obtained Cu@F-GO is obtained. Finally, it is rolled with a roller press and K foil. The binder-free F-GO can be easily separated from the copper foil surface and transferred to the K foil surface, and the copper foil can be recycled. This preparation method is simple, scalable, and suitable for large-scale preparation. Potassium foil covered with F-GO is directly used to assemble button batteries and soft-pack batteries. During the charge and discharge cycle, the deposition of K can promote the breaking of carbon-fluorine bonds and form a fluorine-rich SEI on the surface. The reduced graphene and the formed fluorine-rich SEI act simultaneously to form MES.
[0156] Figure 1As shown in Figure F, the surface structure of MES and Cu foil was studied using SEM and atomic force microscopy (AFM) with Cu foil as the control sample (the surface flatness of K foil after treatment is similar to that of Cu foil). The wrinkled microstructure of the copper foil surface can be intuitively seen through 3D and 2D AFM images, and its surface is undulating and has poor flatness. The SEM image after F-GO material coverage intuitively shows the increase in surface flatness and uniformity. The treated copper foil was also tested and studied using an atomic force microscope. Both 3D and 2D test results show extremely high flatness, which has a positive impact on the initial deposition of the metal.
[0157] like Figure 1 As shown in Figure 1, the electric field strength changes faster at the tip position. There is a tighter potential distribution near the electrode tip, which means that the electric field near the tip is stronger. The existence of the tip effect causes K ions to be attracted by electrostatic forces and accumulate at the tip. In the case of F-GO coverage, the uniformity of the surface field strength is greatly enhanced. Due to the increase in surface flatness, the corresponding distribution of K ions near the surface is also more uniform. The simulation model verifies that the surface electric field becomes more uniform as the surface flatness increases. The uniform interfacial electric field affects the ion distribution and produces uniform deposition on the electrode surface. The improved surface electric field uniformity is beneficial to the initial electroplating of K metal, effectively inhibits the growth of dendrites, prolongs the service life of metal batteries and improves their safety.
[0158] Test Example 2
[0159] like Figure 2 To explore the enhancement of the MES epidermal interface (SEI) structure, a computational study using density functional theory (DFT) was performed to determine whether K deposition could promote the breaking of carbon-fluorine bonds. K, fluorine-doped graphene, KF, and graphene lattice were modeled as the original reactants and products.
[0160] Figure 2 A in the figure shows the lattice parameters of each modeled substrate. Calculations show that the carbon-fluorine bonds of fluorine-doped graphene will automatically break with the contact of K and reduce to KF and graphene. The dynamic insertion of each K atom releases 3.87eV of energy. In the optimized structure, K promotes the breaking of all carbon-fluorine bonds in F-GO to form a graphene layer. As fluorine is completely extracted, the hybrid structure of graphene changes from the initial sp3 hybrid structure to sp2, and the overall structure becomes more planar. The carbon-fluorine Coulomb force of F-GO is weak, and the carbon-fluorine bonds are more easily broken. The increase of fluorine will form a fluorine-rich SEI on the surface, enhancing the mechanical strength and stability of MES. To further verify the changes in fluorine in F-GO, X-ray photoelectron spectroscopy and infrared spectroscopy were used to characterize the materials in different states.
[0161] like Figure 2As shown in Figure B, compared with the original GO, F-GO can introduce fluorine. The test results of the recycled material also show the disappearance of fluorine, which is consistent with the DFT calculation ( Figure 2 C to I). In addition, Figure 2 The infrared spectroscopy results in J also verified the calculation results. The breaking of carbon-fluorine bonds leads to the formation of fluorine-rich SEI on the surface of K metal, which improves the stability of the metal surface and inhibits the growth of dendrites.
[0162] Test Example 3
[0163] In order to further demonstrate the superiority of MES, a more intuitive way was used to observe the surface morphology of K metal. Figure 3 Figure A schematically depicts the different results corresponding to changing different metal electrodes in various ways.
[0164] For bare K, several K components including KF are formed on the surface, but the initially formed SEI is unstable, resulting in uneven K plating and stripping. After a short period, the interface becomes more unstable, which aggravates the growth of dendrites (e.g. Figure 3 The K-metal interface protected by GO can increase the flatness of the metal surface, which is conducive to the uniform deposition of ions. GO can temporarily act as the main body of the metal coating, alleviate the stress changes caused by volume changes, and protect the integrity of the SEI. However, it cannot withstand long-term cycles, and the naturally formed SEI still cannot effectively protect the interface (such as Figure 3 ii in A). In order to improve the interface stability, the interface modification using F-GO improves the surface flatness of the metal negative electrode, making the surface electric field and ion concentration more uniform. The deposition of K metal inside F-GO also alleviates the volume expansion of the interface. K can promote the breaking of carbon-fluorine bonds, release a large amount of fluorine, and form a fluorine-rich SEI surface on the surface. The two-part interface forms MES, which greatly improves the interface stability, enhances the dendrite suppression effect, and significantly improves the cycle life and stability of the battery. The SEM image more intuitively illustrates the effects of the three treatment methods on the K metal surface.
[0165] like Figure 3 As shown in Figure B, under the same test conditions, a large number of dendrites appeared on the exposed K surface. Uneven flux distribution and poor interface stability are direct results. However, after GO surface modification, the problems of dendrites and surface porosity are alleviated, but the problems of dendrites and interface instability still exist. After K deposition on the K metal surface using MES, the surface becomes smoother, solving the problem of loose and porous metal electrodes. It is further proved that MES plays an important role in inhibiting dendrite growth and stabilizing the interface.
[0166] In addition, if Figure 3As shown in C, the dynamic deposition process of K can be directly observed using an in situ optical microscope. Under the same other conditions, the surface morphology changes of three different metal anodes during the deposition process were studied. After 150s of electroplating, multiple dendrite growth points appeared on the bare K surface. Some dendrite growth points appeared on the K@GO surface, while the metal surface protected by MES did not change compared with the initial state. When the electroplating time was extended to 600s, a large number of mossy K and dendrites appeared on the bare K surface, accompanied by the generation of dead K. Although the dendrite points of the GO-modified metal anode did not increase, the dendrite growth rate was extremely fast, which would cause fatal damage to the metal battery. In contrast, the metal anode with MES protection remained dendrite-free. This shows that K is uniformly and densely deposited in the metal anode under the protection of MES, which can inhibit the formation of dendrites during long-term cycling and extend the cycle life of K metal batteries.
[0167] Test Example 4
[0168] To reveal the reaction kinetics of the K anode, symmetric cells fabricated from MES, GO layers (K@MES, K@GO), and bare K electrodes were analyzed by cyclic voltammetry (CV).
[0169] Figure 4 A typical centrosymmetric circuit is shown in Figure 1, reflecting the highly reversible electrochemical behavior of the electrode. Compared with GO and bare K electrodes, the metal electrode with MES shows a more obvious current, demonstrating the reversible plating and stripping of K.
[0170] In addition, the Tafel curve ( Figure 4 Middle (B) shows that the K@MES electrode has a higher exchange current density than the K@GO and bare K electrodes, indicating a higher charge transfer rate.
[0171] Electrochemical impedance spectroscopy (EIS) test shows (such as Figure 4 C) In the comparison of three symmetric cells, the impedance of K@MES is much lower than that of K@GO and bare K. After cycling, the cell composed of K@MES electrodes maintains the smallest interfacial impedance, which is the result of K deposition and SEI formation during cycling (evolution process see Figure 4 (A).
[0172] The rate performance of the symmetrical battery was tested at different surface current densities and surface capacities, such as Figure 4 As shown in D, three relatively symmetrical batteries have current densities of 0.5, 1, 1.5, 2.5, and 3.5 mA cm -1 and deposition capacities of 0.5, 1, 1.5, 2.5, and 3.5 mAh cm -1 K@MES exhibits excellent interfacial properties and fast K +The migration kinetics of K@GO and the excellent dendrite suppression at high current density and areal capacity are shown in Figure 2. In contrast, the cells with K@GO and bare K anodes show larger overpotentials and fluctuations in the plating / stripping voltage curves at high current density. In addition, the symmetric cells composed of K@GO show a higher overpotential at 1.5 mA cm -1 and 1.5 mAh cm -1 The symmetrical battery composed of bare K short-circuited under the test conditions with a slightly increased current density (while the symmetrical battery composed of bare K short-circuited under the test conditions with a slightly increased current density). - 1,1mAh cm -1 Symmetrical cells were assembled using K metals treated with different conditions and tested for long periods of time.
[0173] At a current density of 0.5 mA cm -1 and a deposition capacity of 0.5 mAh cm -1 Under the test conditions (such as Figure 4 E), the plating / stripping life of K@MES is about 2000 hours (3M KFSI in DME). However, the batteries with K@GO and bare K anodes exhibited poor cycle life. The symmetric battery composed of K@GO failed (short circuit) after about 670 hours of cycling, while the symmetric battery of bare K could only cycle normally for 160 hours. This is due to the continued growth of dendrites at the K metal interface, which significantly increased the interface instability and caused the symmetric battery to short circuit rapidly. In the traditional low-concentration electrolyte (0.8M KPF6 in EC / DMC, 1:1), the MES@K symmetric battery still outperformed the other two K anodes ( Figure 4 (F). It is worth noting that different electrolyte systems can show better stability and longer cycle life, which also proves the universality of MES.
[0174] The coulombic efficiency CE of the battery was quantified by preparing an asymmetric K cell, such as Figure 4 As shown in Figure 5G, K|Cu@MES provides more stable cycling performance compared to the lifespan of K|Cu@GO and K|Cu. -1 The CE of the battery dropped sharply due to severe volume expansion and dendrite growth. However, K|Cu@MES stably achieved more than 1600 cycles (more than 3200 hours) under the same test conditions, which is the longest cycle life of this type of battery to date. Benefiting from the double protective layer of MES, the cycle stability of the metal anode is significantly improved.
[0175] also, Figure 4Figure H shows the plating / stripping curves of three different cells under the same cycling conditions. The nucleation overpotential of the asymmetric cell with Cu@MES is lower than that of Cu@GO and bare Cu, which further demonstrates the excellent ability of MES to stabilize the interface.
[0176] Figure 4 Figure 1 shows the cycle life comparison of different metal electrodes. It can be seen that the cycle life of the metal negative electrode K@MES with a surface protective layer is much better than that of the metal electrodes in the prior art.
[0177] Test Example 5
[0178] The same method was used to make MES on the surface of lithium metal and assembled into a symmetrical battery. LiFSI electrolyte was injected at 1 mA cm -2 The current density and 1 mAh cm -2 The cycle life of the symmetrical battery assembled with Li@MES exceeds 4000 hours (e.g. Figure 5 Even with the use of commercial conventional low-concentration electrolyte (0.8M LiPF6 in EC / DEC / DMC), the symmetrical battery composed of Li@MES still has advantages in cycle life and polarization voltage (as shown in Figure 2). Figure 6 shown).
[0179] The coulombic efficiency (CE) of the battery is quantified by preparing a lithium asymmetric battery, such as Figure 7 As shown. Compared with Cu@GO|Li and Cu|Li, Cu@MES|Li exhibits more stable cycling performance and longer cycle time. At the same time, the asymmetric battery made of Cu@MES|Li has a smaller nucleation overpotential (e.g. Figure 7 (B) The rate performance of Li@MES symmetric battery was tested at different surface current density and surface capacity. Figure 7 As shown in C, three relatively symmetrical batteries at current densities of 1, 3, 5, and 10 mA cm -1 and deposition capacities of 1, 3, 5, and 10 mAh cm - 1. Li@MES exhibits excellent interfacial properties and fast Li + These tests not only demonstrate the excellent performance of MES in suppressing dendrites and stabilizing interfaces, but also prove the universality of MES in metal anode applications.
[0180] Test Example 6
[0181] To verify the practical application potential of MES, different metal anodes were matched with Prussian blue cathodes, and conventional KPF6 was used as electrolyte to assemble full batteries. The performance and cycle life of the full batteries were evaluated. -1 The long cycle performance test results under current density are as follows Figure 8 As shown in Figure A, the full battery based on K@MES can provide more than 110 mAh g -1 The reversible capacity of the full battery based on bare K anode and K@GO anode is 2.34W, while other full batteries based on bare K anode and K@GO anode provide lower reversible capacity due to greater polarization. After 500 cycles, the stability of the K metal interface modified by graphene oxide decreases and the coulombic efficiency decreases. The capacity decay of the full battery based on bare K is faster, and the capacity decays to 58 mAh g after 500 cycles. -1 .
[0182] Figure 8 Figure B shows the charge-discharge curve at the end of a long cycle (500th cycle), and there is also a clear capacity gap. The full battery based on K@MES has a smaller polarization, which is due to the advantage of interface stability. In addition, in the rate performance test, the full battery based on K@MES has a higher current density of 500, 1000, 2000, and 3000 mA g -1 The reversible capacities of about 110, 93, 81, and 75 were provided when the other two full batteries were tested under the same conditions. Figure 8 C). The full battery composed of MES-modified K metal also has a smaller polarization voltage under high current density test conditions ( Figure 8 D). Figure 8 As shown in E, the full battery is at 1000mA g -1 The long cycle performance test was carried out at a current density of 1.5000, and the cycle life exceeded 5000 times. Compared with the initial test, the specific capacity has basically not decayed. During the cycle process, the coulombic efficiency of the whole battery exceeded 98%.
[0183] When using KFSI electrolyte, Fig. 9 As shown in Figure 2, K@MES can maintain stable cycling for more than 500 cycles under the same test conditions. Due to interface instability, the coulombic efficiency of full cells based on K@GO and bare K significantly decays after 150 and 100 cycles (Figure 2). Fig. 9 A and B in the figure). The rate performance of full charge is basically consistent with the charge and discharge curve comparison (such as Fig. 9 More importantly, the K@MES-based full cell exhibits ultra-stable long-cycle stability, which makes K-ion batteries promising for real commercial applications.
[0184] In general, the K@MES provided by the present invention exhibits excellent electrochemical performance as the negative electrode of the full battery. The above results show that the MES-modified metal electrode has better electrochemical performance than the GO-modified metal electrode and bare K, which should be attributed to the protection of the metal electrode by MES.
[0185] Test Example 7
[0186] The performance of the batteries prepared in the examples and comparative examples were tested, and the test results are shown in Tables 1 to 3.
[0187] Table 1 Performance test results of Examples 1-3 and Comparative Examples 1-6
[0188]
[0189] Table 2 Performance test results of Examples 4-6 and Comparative Examples 7-12
[0190]
[0191] Table 3 Performance test results of Examples 7-8 and Comparative Examples 13-16
[0192]
[0193]
[0194] In summary, the present invention proposes to use MES to improve the stability of the metal electrode interface by simulating the structure of human skin. F-GO is transferred to copper foil using a simple and effective process, and then easily transferred to the metal electrode surface using a rolling process. During the initial electroplating process, F-GO can accommodate some atoms, which greatly alleviates the volume change of the interface. Alkali metals can promote the breaking of the CF bonds of F-GO to generate a fluoride-rich SEI, thereby improving the mechanical strength of the SEI. At the same time, F-GO generates GO due to the continuous release of fluorine, and GO and fluorine-rich SEI together constitute MES. MES has a high surface flatness and can control the surface electric field strength during the initial cycle. The enhanced interface passivates the highly active metal negative electrode and improves the interface stability during the electroplating / stripping process. The uniform electric field affects the ion concentration, causing the ions to be uniformly deposited on the electrode surface. Therefore, at a current density of 0.5 mA cm -2 and an area capacity of 0.5 mAh cm -2Under the test conditions, the MES-coated metal negative electrode has a plating / stripping life of about 2000 h for the symmetric battery. The cycle life of the Cu@MES|K asymmetric battery exceeds 3200 hours (1600 cycles), which is the longest cycle life of an asymmetric battery to date. This shows that MES can greatly improve the interface stability of the electrode. When matched with the Prussian blue (PB) positive electrode, the entire battery exhibits good cycle stability and rate performance, that is, at 1000 mA g -1 The charge and discharge cycle at a current density of 10000 times has a cycle life of more than 5000 times.
[0195] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A metal electrode having a surface protective layer, characterized in that: It comprises an alkali metal electrode and a surface protection layer supported on the alkali metal electrode, wherein the surface protection layer comprises a graphene layer and a fluorine-containing SEI film, and the graphene layer is located between the alkali metal electrode and the fluorine-containing SEI film; The preparation process of the metal electrode includes: attaching fluorine-doped graphene oxide to the surface of a carrier to form a fluorine-doped graphene oxide layer on the surface of the carrier; transferring the fluorine-doped graphene oxide layer on the surface of the carrier to the alkali metal electrode by rolling; The method also includes using the alkali metal electrode having the fluorine-doped graphene oxide layer as a negative electrode of the battery to perform charge and discharge cycles to form a fluorine-containing SEI film, while converting the fluorine-doped graphene oxide layer into a graphene layer; The process of transferring the fluorine-doped graphene oxide layer on the surface of the carrier to the alkali metal electrode includes: stacking the carrier having the fluorine-doped graphene oxide layer and the alkali metal foil, wrapping the stacked components with a protective film, pressing the stacked components using a roller press, and removing the protective film and the carrier after rolling.
2. The metal electrode according to claim 1, characterized in that: The alkali metal electrode is selected from any one of potassium foil and lithium foil, and the fluorine-doped graphene oxide layer is supported on one side surface of the alkali metal electrode.
3. The metal electrode according to claim 2, characterized in that: The thickness of the alkali metal electrode is 5-50 μm, and the thickness of the fluorine-doped graphene oxide layer is 0.5-2 μm.
4. A method for preparing a metal electrode having a surface protective layer according to any one of claims 1 to 3, characterized in that: include: attaching fluorine-doped graphene oxide to the surface of a carrier to form a fluorine-doped graphene oxide layer on the surface of the carrier; Transferring the fluorine-doped graphene oxide layer on the surface of the carrier to the alkali metal electrode by rolling; The method also includes using the alkali metal electrode having the fluorine-doped graphene oxide layer as a negative electrode of the battery to perform charge and discharge cycles to form a fluorine-containing SEI film, while converting the fluorine-doped graphene oxide layer into a graphene layer; The process of transferring the fluorine-doped graphene oxide layer on the surface of the carrier to the alkali metal electrode includes: stacking the carrier having the fluorine-doped graphene oxide layer and the alkali metal foil, wrapping the stacked components with a protective film, pressing the stacked components using a roller press, and removing the protective film and the carrier after rolling.
5. The preparation method according to claim 4, characterized in that: The carrier is selected from any one of copper foil and aluminum foil.
6. The preparation method according to claim 5, characterized in that: The carrier is copper foil.
7. The preparation method according to claim 4, characterized in that: The preparation process of the fluorine-doped graphene oxide includes: mixing graphene oxide with a dispersant and dispersing the graphene oxide to obtain a dispersion, uniformly mixing a fluoride salt with the dispersion, adding methanol to react, filtering to obtain a fluorinated product, and washing and drying the fluorinated product.
8. The preparation method according to claim 7, characterized in that: The dispersant is o-dichlorobenzene; and the fluoride salt is diethylaminosulfur trifluoride.
9. The preparation method according to claim 8, characterized in that: The concentration of the dispersion is 0.5-2 mg / mL, the volume ratio of the dispersion to the fluoride salt is 50-70:1, and the volume ratio of the dispersion to the methanol is 1-2:
1.
10. The preparation method according to claim 7, characterized in that: The fluoride salt and the dispersion are mixed at -5°C to 5°C, subjected to ultrasonic treatment for 4-8 hours, and then stirred at 15-25°C for 2-4 days.
11. The preparation method according to claim 4, characterized in that: The process of attaching the fluorine-doped graphene oxide to the surface of a carrier comprises: mixing the fluorine-doped graphene oxide with an organic solvent and ultrasonically obtaining a suspension, immersing the carrier in a container filled with water, injecting the suspension on the water surface, and when the suspension forms a self-assembled film on the water surface, lifting the carrier in the water so that the self-assembled film is loaded on the carrier, and obtaining a carrier with a fluorine-doped graphene oxide layer loaded on the surface after drying.
12. The preparation method according to claim 11, characterized in that: After lifting the carrier in the water, the carrier is immersed in water again and lifted up, and the operation is repeated until the thickness of the self-assembled film on the carrier is 0.5-2 μm; wherein the thickness of the carrier is 10-15 μm.
13. The preparation method according to claim 11, characterized in that: The drying process includes: first drying the carrier with the self-assembled film on a hot plate at 70-90° C. for 2-5 minutes, and then drying it in a vacuum oven at 70-90° C. for 8-20 hours.
14. The preparation method according to claim 4, characterized in that: The roller distance is 70%-90% of the total thickness of the stacked assembly, and the rolling speed is 0.5-1.5cm.s -1 .
15. The preparation method according to claim 4, characterized in that: The protective film is a plastic film.
16. An alkali metal battery, characterized in that: The negative electrode is the metal electrode with a surface protective layer as described in any one of claims 1 to 3.
17. The alkali metal battery according to claim 16, characterized in that The preparation process of the negative electrode includes: cutting the metal electrode into a disc shape of 1-2 cm.
18. The alkali metal battery according to claim 16, characterized in that It also includes a positive electrode, an electrolyte and a separator.
19. The alkali metal battery according to claim 18, characterized in that The preparation process of the positive electrode includes: uniformly mixing a conductive agent, a binder and an active material with a dispersing solvent to obtain a slurry, coating the slurry on a copper foil collector, and drying; wherein the mass ratio of the conductive agent, the binder and the active material is 5-7:2-4:
1.
20. The alkali metal battery according to claim 19, characterized in that The conductive agent is acetylene black conductive agent, the adhesive is PVDF adhesive, the active material is Prussian blue material, the dispersing solvent is N-methyl-2-pyrrolidone, and the loading amount of the active material is controlled to be 0.8-1.2 mg.cm during coating. -2 .
21. The alkali metal battery according to claim 18, characterized in that The separator is glass fiber or polypropylene.
Citation Information
Patent Citations
Lithium metal interface protection, preparation method thereof and battery containing lithium metal interface protection
CN110957492A